Types of failures of non-critical components and reliability forecasting of locomotives - Kisselyova, Olga; Abdullayev, Seidulla; Bakyt, Gabit; Baubekov, Yermek; Altayeva, Zhanar (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this article is to consider the main types of failures of load-bearing parts of traction rolling stock, which have a significant impact on the operational reliability and safety of railway transport. In the bearing components of the mechanical part of locomotives, both gradual and sudden failures may occur. The analysis of the causes of failures, fatigue failures, wear, corrosion damage, and manufacturing defects has been performed. Gradual failures arise due to the accumulation of fatigue damage. The methods of increasing the life of the bearing elements and improving the design are proposed. Sudden failures are defined as those associated with a reduction in the safety margin of long-term (static) or impact strength below the permissible value. According to these studies, the probability of a sudden failure is determined as the probability that the random value of the applied static stress exceeds the random value of some characteristic of the material's strength, σR, which refers to the yield strength or tensile strength, σb. The results of this study can be used in the development of technical measures for the maintenance and repair of locomotives.